2016
DOI: 10.3732/ajb.1500248
|View full text |Cite
|
Sign up to set email alerts
|

Pollen structure and function in caesalpinioid legumes

Abstract: In Detarieae and Cercideae in particular, there is potential to utilize pollen characters to estimate pollination systems where these are unknown. Supratectal verrucae and gemmae have apparently evolved iteratively in Cercideae and Detarieae. At the species level, there is a potential correlation between striate/verrucate patterns and vertebrate pollination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 69 publications
(106 reference statements)
2
22
0
Order By: Relevance
“…Therefore, it seems evident that stigma shape and organization are highly associated with the type of pollination (Edlund et al, 2004). However, much greater effort has been expended on elucidating the relationship between pollen and pollination (e.g., Banks and Rudall, 2016;Hesse, 2000;Osborn et al, 1991) than between stigma and pollination (Heslop-Harrison, 1992). The study of the diversity of stigmata related to various types of pollination (Basso-Alves et al, 2011;Jousselin and Kjellberg, 2001) and breeding systems (Katinas et al, 2016;Lora et al, 2011) is thus of great interest in general and for obligate mutualisms such as between fig trees (Ficus) and their agaonid pollinating wasps in particular (Galil and Eisikowitch, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems evident that stigma shape and organization are highly associated with the type of pollination (Edlund et al, 2004). However, much greater effort has been expended on elucidating the relationship between pollen and pollination (e.g., Banks and Rudall, 2016;Hesse, 2000;Osborn et al, 1991) than between stigma and pollination (Heslop-Harrison, 1992). The study of the diversity of stigmata related to various types of pollination (Basso-Alves et al, 2011;Jousselin and Kjellberg, 2001) and breeding systems (Katinas et al, 2016;Lora et al, 2011) is thus of great interest in general and for obligate mutualisms such as between fig trees (Ficus) and their agaonid pollinating wasps in particular (Galil and Eisikowitch, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Ferguson & Pearce (1986) described two patterns of morphological variation in pollen and found that apertures and exine stratification correlated with taxonomy, whereas ornamentation, pollen size and exine thickness showed a great deal of continuous variation and also examples of homoplasy. In many cases homoplasious morphological variation is correlated with floral morphology and pollination syndromes (e.g., supratectal gemmae and verrucae appeared to be correlated with bat pollination) (Ferguson & Pearce 1986) and has evolved iteratively in the tribes Cercideae and Detarieae (Banks & Rudall 2016).…”
Section: Proposal To Recognise Phanera Sect Corymbosae As a Distinctmentioning
confidence: 99%
“…2B). However, similar types of verrucate ornamentation have previously been seen in taxa pollinated by butterflies, moths, birds or bats (Banks & Rudall 2016). Hao et al (2003) constructed a well resolved phylogeny of the subtribe Bauhiniinae (sensu Wunderlin 1979) in which 7 accessions were sampled that represented 5 species from sect.…”
Section: Proposal To Recognise Phanera Sect Corymbosae As a Distinctmentioning
confidence: 99%
“…Pollen walls must accommodate great contraction and expansion of the male gametophyte during pollen desiccation in the anther, presentation and dispersal, and upon rehydration on the stigma (Heslop‐Harrison, 1979). Banks and Rudall (2016, in this issue) explore the diversity of pollen structure and function among all 171 genera of the paraphyletic caesalpinioid legumes (the species‐rich papilionoid and mimosoid legumes are currently nested within the caesalpinioid clade, but were not studied). In this survey, 102 of 120 distinctive pollen morphologies were present in the two early‐divergent caesalpinioid tribes, Cercideae and Detarieae, compared with only 19 morphologies in the remaining two tribes (despite similar species numbers).…”
Section: What Specific Pollen Traits Affect Male Gametophyte Performamentioning
confidence: 99%